ANALISIS MENURUNNYA TEKANAN LUBRICATING OIL PADA DIESEL GENERATOR DI KM. DHARMA KARTIKA VII - Dolly Sirait, Maruli; Nugroho, Azis; Sandi, Wulan Marlia; Zainuddin, Mochammad; Kristiyono, Antonius Edy (Penerbit Lafadz Jaya, 2026)
Diesel generators are vital components in a ship's machinery system that converts mechanical energy into electrical energy. Diesel generators serve as the primary source of electrical power for various onboard needs, such as ship operations, navigation, communications, comfort, and other equipment. The lubrication system (lubricating oil) is a special liquid that plays a crucial role in lubricating engine components, ensuring smooth engine operation, and maintaining the performance and reliability of diesel generator engines. A decrease in lubricating oil pressure can cause overheating, increased friction between components, and even overall engine damage. This study aims to analyze the causes of the decrease in lubricating oil pressure in the diesel generator on the KM. Dharma Kartika VII ship and its handling efforts. The method used is a descriptive qualitative approach with data collection techniques through direct observation, interviews with engineers, documentation, and literature studies. The results of this study are expected to serve as a practical reference for ship crews and maritime cadets in handling disturbances in the diesel generator lubrication system appropriately.